M2-Deficient Single-Replication Influenza Vaccine–Induced Immune Responses Associated With Protection Against Human Challenge With Highly Drifted H3N2 Influenza Strain . (29th July 2021) - Eiden, Joseph; Volckaert, Bram; Rudenko, Oleg; Aitchison, Roger; Herber, Renee; Belshe, Robert; Greenberg, Harry; Coelingh, Kathleen; Marshall, David; Kawaoka, Yoshihiro; Neumann, Gabriele; Bilsel, Pamuk
Abstract: Background: Current influenza vaccines are strain specific and demonstrate low vaccine efficacy against H3N2 influenza disease, especially when vaccine is mismatched to circulating virus. The novel influenza vaccine candidate, M2-deficient single replication (M2SR), induces a broad, multi-effector immune response. Methods: A phase 2 challenge study was conducted to assess the efficacy of an M2SR vaccine expressing hemagglutinin and neuraminidase from A/Brisbane/10/2007 (Bris2007 M2SR H3N2; clade 1). Four weeks after vaccination, recipients were challenged with antigenically distinct H3N2 virus (A/Belgium/4217/2015, clade 3C.3b) and assessed for infection and clinical symptoms. Results: Adverse events after vaccination were mild and similar in frequency for placebo and M2SR recipients. A single dose of Bris2007 M2SR induced neutralizing antibody to the vaccine (48% of recipients) and challenge strain (27% of recipients). Overall, 54% of M2SR recipients were infected after challenge, compared with 71% of placebo recipients. The subset of M2SR recipients with a vaccine-induced microneutralization response against the challenge virus had reduced rates of infection after challenge (38% vs 71% of placebo recipients; P = .050) and reduced illness. Conclusions: Study participants with vaccine-induced neutralizing antibodies were protected against infection and illness after challenge with an antigenically distinct virus. This is the first demonstration of vaccine-induced protection against a highly drifted H3N2 challenge virus. Abstract : In this phase 2 challenge study, intranasal vaccination with M2-deficient single-replication vaccine expressing A/Brisbane/10/2007 hemagglutinin and neuraminidase (clade 1) induced protective immunity, preventing infection and disease and reducing viral shedding after challenge with a highly drifted A/Belgium/4217/2015 (clade 3C0.3b) influenza virus.